2015
DOI: 10.1007/s00403-015-1611-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of IL36RN mutation with different clinical features of pustular psoriasis in Chinese patients

Abstract: Different studies have reported various values for the percentage of patients with IL36RN mutations, and it has also been reported that the sites of these mutations differ among different ethnicities. The current study was a cross-sectional study conducted to investigate the risk factors predicting IL36RN mutation in Chinese patients with different clinical features of pustular psoriasis. 57 Han Chinese patients, including 32 with generalized pustular psoriasis, 14 with palmoplantar pustulosis, 9 with plaque-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 22 publications
10
81
2
1
Order By: Relevance
“…Likewise, our group and others have identified homozygous or composite heterozygous loss‐of‐function mutations the IL36RN gene in consanguineous families from southern Tunisia (Fig. b), and also in sporadic or familial cases of GPP from Europe and from Asia …”
Section: Immunopathogenesis: the Big Bang Of Genetic Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…Likewise, our group and others have identified homozygous or composite heterozygous loss‐of‐function mutations the IL36RN gene in consanguineous families from southern Tunisia (Fig. b), and also in sporadic or familial cases of GPP from Europe and from Asia …”
Section: Immunopathogenesis: the Big Bang Of Genetic Studiessupporting
confidence: 68%
“…1b), and also in sporadic or familial cases of GPP from Europe and from Asia. 11,[18][19][20][21][22][23] These mutations, which are most commonly identified in patients with GPP without plaque psoriasis, impair structure and/or expression and ultimately the regulatory function of the encoded interleukin (IL)-36Ra protein, leading to an enhanced inflammatory cascade downstream of the interaction between the IL-36a, IL-36b and IL-36c agonistic ligands and their specific receptor. This results, mainly in keratinocytes and macrophages, to the upregulated expression and extracellular release of inflammatory mediators such as CXCL8/IL-8, tumour necrosis factor (TNF)-a, IL-1 and IL-23.…”
Section: Immunopathogenesis: the Big Bang Of Genetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same pattern was confirmed by a European study finding IL36RN mutations in 46% of GPP patients without PV and 17% in GPP with PV [15]. Finally, an interesting study from China found that about 93% of patients with GPP and features of ACH had a damaging IL36RN mutation [16].…”
Section: Accepted Articlesupporting
confidence: 66%
“…Although GPP in childhood has been regarded as less recalcitrant with a more benign course, higher rates of spontaneous resolution and long‐term remission compared with adult patients, it still can be life‐threatening in children . Homozygous or compound heterozygous mutations in the IL‐36 receptor antagonist gene IL36RN is present in 75% of GPP cases, and the most common mutation is c.115+6T>C in the Han Chinese patients in Taiwan …”
Section: Discussionmentioning
confidence: 99%